2010
DOI: 10.1029/2010ja015638
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐based estimates of outer radiation belt energetic electron precipitation fluxes into the atmosphere

Abstract: [1] AARDDVARK data from a radio wave receiver in Sodankylä, Finland have been used to monitor transmissions across the auroral oval and just into the polar cap from the very low frequency communications transmitter, call sign NAA (24.0 kHz, 44°N, 67°W, L = 2.9), in Maine, USA, since 2004. The transmissions are influenced by outer radiation belt (L = 3-7) energetic electron precipitation. In this study, we have been able to show that the observed transmission amplitude variations can be used to determine routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 33 publications
9
107
0
Order By: Relevance
“…Thus, the use of any POES observations as a measure of electron precipitation into the atmosphere needs to be carefully considered. In order to constrain the POES observations, Clilverd et al (2010) have demonstrated the potential of using ground-based observations of changes in ionospheric D-layer ionisation (VLF, very low frequency radio propagation) to establish near-real-time electron precipitation fluxes. For the time being, inclusion of electron precipitation and thus full EPP forcing in model simulations is yet to reach the same routine approach as solar protons (SPEs).…”
Section: Energetic Particle Precipitationmentioning
confidence: 99%
“…Thus, the use of any POES observations as a measure of electron precipitation into the atmosphere needs to be carefully considered. In order to constrain the POES observations, Clilverd et al (2010) have demonstrated the potential of using ground-based observations of changes in ionospheric D-layer ionisation (VLF, very low frequency radio propagation) to establish near-real-time electron precipitation fluxes. For the time being, inclusion of electron precipitation and thus full EPP forcing in model simulations is yet to reach the same routine approach as solar protons (SPEs).…”
Section: Energetic Particle Precipitationmentioning
confidence: 99%
“…The locations of the Finnish chain of riometer stations and their L-values are tabulated in Table 1. A riometer responds to the integrated absorption of cosmic ray noise through the ionosphere (Clilverd et al 2010) where the particle motion is collision dominated. The riometers are widebeam, typically 30 MHz and sensitive to any incident particle population capable of reaching the ionosphere in the range of 70 -100 km (that is, D-region).…”
Section: The Imaging Riometer Absorption Datamentioning
confidence: 99%
“…They obtained negative phase and amplitude variations of the VLF signal both during day and nighttimes during the main storm phase days, but the nighttime variations were more pronounced. There have not been other studies on magnetic storm associated subionospheric changes purely at low latitude paths; however, there have been several studies on VLF perturbations due to storm-induced energetic electron precipitation at mid and high latitudes (e.g., Peter et al 2006;Clilverd et al 2010).…”
Section: Introductionmentioning
confidence: 99%